Creation of Highly Dispersed Supported Polyoxometalate Cesium Salts via Cation Exchange from Alkylammonium Salts on Supports. Issue 2 (30th November 2022) - Suzuki, Takaaki; Yabe, Tomohiro; Wachi, Keiju; Yonesato, Kentaro; Suzuki, Kosuke; Yamaguchi, Kazuya
Abstract: We have reported several precisely designed metal‐oxo clusters on lacunary polyoxometalate (POM) tetra‐ n ‐butylammonium (TBA) salts in organic solvents. However, owing to their low thermostability and/or low effective surface area, POM TBA salts are not amenable to heterogeneous catalysts for gas‐phase reactions at high temperature. To avoid this problem, we developed a new preparation method that obtains highly dispersed supported‐POM Cs salts (Cs−POM/support) via cation exchange from the corresponding TBA salts on supports. In this study, a model Keggin‐type POM called TBA4 PVMo11 O40 (TBA−PVMo11) is supported on oxides (TBA−PVMo11/support) using an incipient wetness method in acetonitrile. This TBA−PVMo11/support was cation‐exchanged with cesium trifluoromethanesulfonate in ethanol to obtain supported‐POM Cs salts (Cs−PVMo11/support). Various characterizations revealed that the TBA−PVMo11/support maintained the original Keggin structure during cation exchange and that Cs−PVMo11 was highly dispersed on the supports. Furthermore, Cs−PVMo11/support maintained the Keggin structure even after calcination at 573 K under an aerobic condition. Abstract : A new preparation method was developed to obtain supported polyoxometalate Cs salts by cation exchange from the corresponding tetra‐ n ‐butylammonium salts on supports using cesium trifluoromethanesulfonate in ethanol. Various characterizations revealed that the polyoxometalate cesium salts were dispersedly supported on oxide supports (especially Al2 O3 ) while maintaining the original Keggin structure.